2016
DOI: 10.3892/etm.2016.3974
|View full text |Cite
|
Sign up to set email alerts
|

Determination of DNA damage and telomerase activity in stanozolol-treated rats

Abstract: Anabolic androgenic steroids (AAS) are performance-enhancing drugs commonly abused by atheletes. Stanozolol is a synthetic testosterone-derived anabolic steroid. Although it is well known that AAS have several side-effects, there are only few toxicological studies available on the toxic effects and mechanisms of action of stanozolol. The aim of this study was to investigate the genotoxic effects of stanozolol and to determine its effects on telomerase activity in Sprague-Dawley male rats. For this purpose, 34 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Other mechanisms hypothesized involved DNA-damage at different levels include: micronuclei formation [ 34 , 42 ], DNA methylation [ 36 ], ROS-mediated DNA covalent binding [ 39 ], and alterations in telomerases [ 44 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other mechanisms hypothesized involved DNA-damage at different levels include: micronuclei formation [ 34 , 42 ], DNA methylation [ 36 ], ROS-mediated DNA covalent binding [ 39 ], and alterations in telomerases [ 44 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of these agents has been proven high-dose nandrolone exposition, which determines a significant DNA damage in blood, liver, bone marrow, brain and testicle cells in experimental animals exposed [ 43 ]. On the other hand, AAS can elicit profound modifications in genetic sequences by means of alterations in telomerase activity [ 44 ]. Nourbakhsh et al [ 45 ], tried to verify the implications of androgens in ovarian carcinogenesis.…”
Section: From Aas Genotoxicity To Carcinogenicitymentioning
confidence: 99%
“…Even though the mechanisms responsible for stanozolol-induced hepatotoxicity have not yet been clearly identified, proliferative effects on liver cells may play a central role in the observed hepatotoxicity ( 12 , 40 , 41 ). In our previous study, we demonstrated that stanozolol exerted DNA-damaging effects in peripheral blood lymphocytes, probably related to telomerase activity alterations ( 35 ). Although various environmental factors are known to up- and downregulate telomerase activity, the effects of exercise on telomerase activity have not yet been clearly identified ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that physical exercise increases telomerase activity in different cell types ( 52 , 53 ). However, to the best of our knowledge, there is no study available to date investigating the effects of stanozolol on telomerase activity in the presence/absence of exercise, apart from our previous study which focused on circlulating telomerase activity in peripheral blood mononuclear cells (PBMCs) ( 35 ). Our results indicated the elevation of telomerase activity and TERT expression in the liver tissue, which could be associated either with an increased proliferation risk due to stanozolol treatment ( 10 ), rather unlikely for such a short exposure period, or may represent a counteracting mechanism ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation